Problematika Pembelajaran Bahasa Arab di Sekolah Tinggi Agama Islam (STAI) Syaichona Moh. Cholil Bangkalan - Humaidi . (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2017)
Learning Arabic language is not easy matter, but if it is followed by recitation and research will find many methods and strategies for learning more effective and fast. The purpose of this research are: (1) For knowing the difficulties of learning Arabic language. (2) For knowing the factors happened learning Arabic language. (3) For knowing the difficulty solution of learning Arabic language at Islam religion colleague of Syaichona Moh. Cholil Bangkalan. In this research, the writer used approach of qualitative research by using recitation model of analysis descriptive. The collecting data used interview method, observation, and documentation. Meanwhile the data analysis in this research used model analysis of mils and hubberman. It appropriated with the result research, found the difficulties of learning Arabic language as followed: the individual ability difference of Arabic language that is very far away, the difficulties in making Arabic language environment, the difficulties for lecturer to be same the student abilities, and finally it is less for using the facility of modern technology. Meanwhile the factors happened the difficulties that are such as: the difference of education background for university students between the student of Islamic boarding school and not Islamic boarding school, the minimum of having the happy feeling or curious for Arabic language, seldom held the meeting between the first semester with others for making Arabic language environment. The solution for solving the difficulties of learning Arabic language is such as: The lecturer divide into groups that are suitable with university student's ability in the class, the lecturer gives guidance and additional lesson for improving student's Arabic language, in teaching, the lecturer is demanded to choose the interest medium and unique method in order that the university student tends interesting for learning Arabic language, holding meeting program with all levels of semester to create Arabic language environment well, in teaching, the lecturer is demanded to pay attention the education background of university student between Islamic boarding school student and not Islamic boarding school.